Multiaxial creep deformation investigation of miniature cruciform specimen for type 304 stainless steel at 923 K using non-contact displacement-measuring method - Hiyoshi Noritake (Journal of the Mechanical Behavior of Materials)
Multiaxial creep investigations at high temperatures are required to guarantee the integrity of structural materials such as boiler pipes for power generation and turbine blades for aviation and industrial applications. The multiaxial creep testing method using a cruciform specimen has several advantages, and the authors successfully downsized the specimen. The authors also developed a technique for the in situ observation of the specimen in an electric furnace and the non-contact displacement measurement in the development of a biaxial tensile creep testing machine for the miniature cruciform specimen. By observing the specimen at a target mark during the creep testing through an observation window installed at the bottom of the furnace, it was possible to visualize the specimen surface variations and obtain the axial strain from the locus of the target marks. The Mises-type equivalent strain was calculated from the axial strains obtained in the equi-biaxial tensile multiaxial creep testing and was compared with the strains obtained in the uniaxial creep testing. The Mises-type equivalent strain can be expressed using a unified method up to approximately 5% of the initial strain in the test, even in the multiaxial stress state.